Application of the Extracts of Punica granatum in Oral Cancer: Scoping Review - Mario Dioguardi; Andrea Ballini; Diego Sovereto; Francesca Spirito; Angela Pia Cazzolla; Riccardo Aiuto; Vito Crincoli; Giorgia Apollonia Caloro; Lorenzo Lo Muzio (MDPI AG, 2022)
The Punica granatum L. is an ancient fruit plant native to south-western Asia. It belongs to the Litraceae family and of its genus we have only one other Punica protopunic species. The fruit is rich in polyphenols, whose extract is consumed as a food and is considered safe. In medicine, it is used for its antioxidant properties; it has a rich component of tannic polyphenols among which the most bioactive are: punicalagin (flavonoids) and anthocyanins (delphinidin, cyanidin, pelargonidin), which are found mainly in the skins and in the pericarp; however, all the parts of the Punica granatum are used for therapeutic purposes as anti-inflammatories and analgesics and in diabetes and cardio-vascular disease. Punica granatum extracts also show interesting anticancer activities in influencing tumorgenesis and angiogenesis and cell transformation and proliferation. The purpose of this scoping review is to summarize all the scientific evidence on the possible applications of Punica granatum extracts in the treatment and prevention of oral cavity tumors to investigate the anticancer properties of the active ingredients extracted from Punica granatum. Methods: The scoping review was carried out following the PRISMA-ScR checklist; the search was performed on three databases (Scopus, Science direct and PubMed) and one registry (Cochrane library). Results: The search produced a number of bibliographic sources equal to 11,403; with the removal of duplicates, 670 potentially admissible articles were obtained, from 24 of which only 7 in vitro studies on OSCC cell lines were included. Conclusions: From the preliminary data on the cellular lines of OSCC, it emerges that for oral cancer there are conditions for which the extracts of Punic granatum are effective at least from a prevention perspective.